Characterization of tenascin-C as a novel biomarker for asthma: utility of tenascin-C in combination with periostin or immunoglobulin E - Mina Yasuda; Norihiro Harada; Sonoko Harada; Ayako Ishimori; Yoko Katsura; Yukinari Itoigawa; Kei Matsuno; Fumihiko Makino; Jun Ito; Junya Ono; Kazunori Tobino; Hisaya Akiba; et al. (Allergy, Asthma & Clinical Immunology, 2018)
Abstract Background Extracellular matrix proteins tenascin-C (TNC) and periostin, which were identified as T-helper cell type 2 cytokine-induced genes in human bronchial epithelial cells, accumulate in the airway basement membrane of asthmatic patients. Although serum periostin has been accepted as a type 2 biomarker, serum TNC has not been evaluated as a systemic biomarker in asthma. Therefore, the objective of this study was to evaluate whether serum TNC can serve as a novel biomarker for asthma. Methods We evaluated 126 adult patients with mild to severe asthma. Serum TNC, periostin, and total IgE concentrations were quantified using enzyme-linked immunosorbent assays. Results Serum TNC levels were significantly higher in patients with severe asthma and high serum total IgE levels. Patients with both high serum TNC (> 37.16 ng/mL) and high serum periostin (> 95 ng/mL) levels (n = 20) or patients with both high serum TNC and high serum total IgE (> 100 IU/mL) levels (n = 36) presented higher disease severity and more severe airflow limitation than patients in other subpopulations. Conclusions To our knowledge, this is the first study to show that serum TNC levels in asthmatic patients are associated with clinical features of asthma and that the combination of serum TNC and periostin levels or combination of serum TNC and total IgE levels were more useful for asthma than each single marker, suggesting that serum TNC can serve as a novel biomarker for asthma.